The effect of fine particle removal from ground forage samples on In Saccro dry matter and neutral detergent fiber disappearance values - Mack, Claudia Isabell (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.